2015
DOI: 10.1111/adb.12237
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity in young smokers: a tract-based spatial statistics study

Abstract: Previous diffusion tensor imaging (DTI) studies revealed contradictory effects of smoking on fractional anisotropy (FA). Multiple DTI-derived indices may help to deduce the pathophysiological type of white matter (WM) changes and provide more specific biomarkers of WM neuropathology in the whole brain of young smokers. Twenty-three young smokers and 22 age-, education- and gender-matched healthy non-smoking controls participated in this study. Tract-based spatial statistics was employed to investigate the WM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 48 publications
7
50
1
Order By: Relevance
“…Typically, the loss of myelin is associated with greater radial diffusion, or water diffusion perpendicular to the axon, and less axial diffusion, or water diffusion parallel to the axon; reviewed in (Mori and Zhang, 2006). Thus, findings from Yu et al (2015) of decreased radial diffusivity accompanied by increased axial diffusivity within tracts including the internal and external capsules are consistent with the notion of an increase in myelination among adolescent smokers (although more direct evidence is needed to support this hypothesis). However, as this study only included male smokers, additional studies assessing multiple indices of white matter in both male and female adolescent and young adult smokers are needed to confirm and extend these findings.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Typically, the loss of myelin is associated with greater radial diffusion, or water diffusion perpendicular to the axon, and less axial diffusion, or water diffusion parallel to the axon; reviewed in (Mori and Zhang, 2006). Thus, findings from Yu et al (2015) of decreased radial diffusivity accompanied by increased axial diffusivity within tracts including the internal and external capsules are consistent with the notion of an increase in myelination among adolescent smokers (although more direct evidence is needed to support this hypothesis). However, as this study only included male smokers, additional studies assessing multiple indices of white matter in both male and female adolescent and young adult smokers are needed to confirm and extend these findings.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, increased FA among adolescent/young adult smokers may be a consequence of exposure to nicotine. Consistent with this interpretation, positive associations between pack years and FA values within the genu (Jacobsen et al, 2007) and corona radiata (Yu et al, 2015) were reported among adolescent/young adult smokers. In contrast to this, negative associations between FTND scores and FA values within the anterior cingulum (Huang et al, 2013) and corona radiata (Yu et al, 2015) were also reported.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations